Outbond as the Basis of Multiple Intelligences Learning Activity - Sari, Yulvia; Sutarto, Joko; Hartono, Hartono (Universitas Negeri Semarang, 2018)
Every chidren has various kinds of intellegence. As they get older, their intelligence also has been developed . In this case, It is necessary to provide proper stimulation. So on their intellegence can be optimally developed. One of effective stimulation is outbound activities. Through outbond activities, children will be stimulated their bodily-kinesthetic intelligence, intrapersonal intelligence, and naturalist intelligence which are needed by them when interacting with their surroundings. The aim of this study was to analyze intepersonal, bodily kinestic intelligence, and naturalist intelligence of children in outbond activities that has been held in PAUD (TK B) Alam Ar Ridlo Tembalang Semarang. The approach of this study was qualitative. The collected data was carried out through observation, interview, and documentation. The data was validated through data source triagulation, theory triagulation, and triagulation of review information. To analyze data, this study used three techniques, 1) data reduction, 2) data presentation, and 3) conclusion and its verification. This study that was held in PAUD (TK B) Alam Ar Ridlo Tembalang Semarang shows that outbond activities can stimulate children’s interpersonal intelligence, bodily-kinesthetic intelligence, and naturalist intelligence.